2009
DOI: 10.17221/259-pse
|View full text |Cite
|
Sign up to set email alerts
|

Changes in photosynthetic pigment and carbohydrate content in common bean cultivars infected by Colletotrichum lindemuthianum

Abstract: The aim of this study was to investigate the changes in photosynthetic pigments and carbohydrate contents on resistant and susceptible plants of Phaseolus vulgaris L. (cvs. Mexico 222 and Widusa) infected by Colletotrichum lindemuthianum race 23. The experimental design used was entirely randomized in factorial scheme, with 2 cultivars (Mexico 222 and Widusa) and 2 treatments (control and inoculated). The cultivar Widusa (susceptible) showed a significant reduction in photosynthetic pigments, and an increase i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 10 publications
1
5
0
4
Order By: Relevance
“…Reduction of chlorophyll caused a decrease in the photosynthesis rate of infected plants in our study. Lobato et al (2009a) described similar results in Phaseolus vulgaris plants infected by Colletotrichum lindemuthianum race 23. Berova et al (2007) compared four cultivars of Phaseolus vulgaris infected by two bacteria (Xanthomonas campestris and Pseudomonas syringae) and found that chlorophyll a and b were negatively affected.…”
Section: Photosynthesis and Photosynthetic Water Use Efficiencysupporting
confidence: 70%
See 1 more Smart Citation
“…Reduction of chlorophyll caused a decrease in the photosynthesis rate of infected plants in our study. Lobato et al (2009a) described similar results in Phaseolus vulgaris plants infected by Colletotrichum lindemuthianum race 23. Berova et al (2007) compared four cultivars of Phaseolus vulgaris infected by two bacteria (Xanthomonas campestris and Pseudomonas syringae) and found that chlorophyll a and b were negatively affected.…”
Section: Photosynthesis and Photosynthetic Water Use Efficiencysupporting
confidence: 70%
“…Under favourable conditions such as high temperature and humidity, this fungus can infect the common bean crop in all growth stages (Broughton et al 2003). In addition, this pathogen causes morphological, physiological and biochemical alterations that have been described previously in Phaseolus vulgaris, such as the significant decrease in photosynthetic pigments (Lobato et al 2009a), photosynthesis rate (Lopes & Berger 2001) and consequent yield reduction ). Other disorders in carbon and nitrogen metabolism have also been reported by Lobato et al (2009b) and Gonc¸alves-Vidigal et al (2009b).…”
Section: Introductionmentioning
confidence: 80%
“…It has been reported that the effect of microbial inoculants on the photosynthetic pigments of plants may be different for phytopathogenic and plant-growth-promoting microorganisms. Inoculation of plants with pathogenic microorganisms (e.g., fungus Colletotrichum lindemuthianum and the bacteria Uromyces appendiculatus and Xanthomonas campestris) was reported to decrease chlorophyll and carotenoid content in legumes (Berova et al 2007;Lobato et al 2009;Lopes and Berger 2001). In contrast, inoculation of stressed plants with plant-growth-promoting microorganisms, e.g., Rhizobium sp., Bacillus subtilis, and Pseudomonas fluorescens, resulted in increases in chlorophyll and carotenoid content (Dell'Amico et al 2008;Mohamed and Gomaa 2012;Wani and Khan 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Plant productivity is quite sensitive to various stress factors of both biotic and abiotic nature [19]. The observed pronounced decrease in growth and pigments at the infected plants in several reports [20][21][22][23][24][25]. Faheed et al [26] mentioned that, infected tomato seedlings with Alternaria solani showed highly significant decrease in the contents of chlorophyll a, chlorophyll b, carotenoids and consequently total pigments compared to the control.…”
Section: Introductionmentioning
confidence: 99%